2019
DOI: 10.3346/jkms.2019.34.e212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Institutional Case Volume on In-Hospital and Long-Term Mortality in Critically Ill Patients Requiring Mechanical Ventilation for 48 Hours or More

Abstract: Background The purpose of this study was to evaluate whether institutional case volume affects clinical outcomes in patients receiving mechanical ventilation for 48 hours or more. Methods We conducted a nationwide retrospective cohort study using the database of Korean National Healthcare Insurance Service. Between January 2007 and December 2016, 158,712 adult patients were included at 55 centers in Korea. Centers were categorized according to the average annual number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…However, there is a paucity in published studies on how hypertension affects clinical outcome in patients with sepsis. We found that hypertension had lower in-hospital mortality than other comorbidities, in line with previous ICU studies [ 19 , 20 ]. A retrospective study demonstrated that patients with septic shock and chronic hypertension achieved and maintained target mean arterial pressure (MAP) more quickly, but that faster target MAP attainment and maintenance did not translate into lower mortality [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, there is a paucity in published studies on how hypertension affects clinical outcome in patients with sepsis. We found that hypertension had lower in-hospital mortality than other comorbidities, in line with previous ICU studies [ 19 , 20 ]. A retrospective study demonstrated that patients with septic shock and chronic hypertension achieved and maintained target mean arterial pressure (MAP) more quickly, but that faster target MAP attainment and maintenance did not translate into lower mortality [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Its prevalence exceeds 13% in the US [ 36 ] and 8.2% in Korea adult population [ 37 ]. Moreover, observational studies reported a 10% to 13.3% prevalence in ICU patients [ 19 , 38 ], similar to the 13.7% in our patients with sepsis. The majority of studies reported variable in-hospital mortality rates for patients with CKD ranging from 28% to 45% [ 9 , 10 ], which is in line with our results, at 28%.…”
Section: Discussionsupporting
confidence: 89%
“…As mentioned earlier, hospitals with higher ED levels and more staffed beds cared for more critically ill patients. Increasing evidence suggests that hospitals with higher patient volumes achieve better patient outcomes across various medical conditions and surgical procedures [ 60 63 ]. Our findings may reflect this “volume-outcome relationship”.…”
Section: Discussionmentioning
confidence: 99%
“…Tables 1 - 3 summarized studies that evaluated the impact of ICU case volume on patient outcome in general critically ill patients ( Table 1 ) [ 10 - 13 ], sepsis and septic shock patients ( Table 2 ) [ 14 - 19 ], and mechanically ventilated patients ( Table 3 ) [ 20 - 26 ].…”
Section: The Impact Of Institutional Case Volume On Various Criticall...mentioning
confidence: 99%
“…The in-hospital mortality rates for the low-, medium-, and high-volume groups were 39.2%, 35.8%, and 32.6%, respectively (P<0.01). After adjusting for covariates, the low-volume centers exhibited a significantly higher mortality rate than the high-volume centers (OR, 1.33; 95% CI, 1.30–1.37; P<0.001) [ 26 ]. A similar inverse relationship between case volume and long-term mortality was observed when comparing 5-year mortality rates between low- and high-volume centers (OR, 1.26; 95% CI, 1.20–1.31; P<0.001).…”
Section: The Impact Of Institutional Case Volume On Various Criticall...mentioning
confidence: 99%